Decreased inhibin B responses following recombinant human chorionic gonadotropin administration in normal women and women with polycystic ovary syndrome - Shayya, Rana F.; Rosencrantz, Marcus A.; Chuan, Sandy S.; Cook-Andersen, Heidi; Roudebush, William E.; Irene Su, H.; Shimasaki, Shunichi; Chang, R. Jeffrey (Fertility and sterility, 2014)
To determine whether granulosa cells contribute to excess androgen production, by assessing inhibin B (Inh B) responses to hCG in women with polycystic ovary syndrome (PCOS) and in normal women. Prospective study. Academic medical center. Twenty women with PCOS and 16 normal women. Blood samples obtained before and 24 hours after injection of 25 μg recombinant hCG (r-hCG). Basal and stimulated Inh B, E2, androstenedione (A), and T responses after r-hCG administration. In normal and PCOS women, r-hCG induced a significant reduction of Inh B levels. Lowered Inh B responses were not related to body mass index, PCOS status, or age by multivariate regression. Recombinant hCG significantly increased serum A and E2 in both normal and PCOS women. In normal and PCOS women, Inh B production was decreased following r-hCG administration. These findings strongly suggest that in PCOS women androgen excess is not enhanced by LH-stimulated Inh B production. NCT00747617.